Kilka uwag o słowie w tekstach Jana Pawła II - Piotrowicz, Anna (Słowo. Studia językoznawcze, 2010)
The Author analyses some various texts by John Paul II and shows how a word functions in them. The parts of this article are: The Word in paraphrases of God and Jesus Christ; The Word as the beginning and the threshold; What somebody’s word can do?; What is the word like?; Freedom of word (speech); Pope’s word in the metalinguistic constructions; Pope’s word in the phraseological constructions.